2022
DOI: 10.1097/ogx.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adenomyosis on Pregnancy and Pregnancy Outcomes: A Review

Abstract: ObjectiveThe aim of this review was to describe the risk factors, diagnosis, and effects on pregnancy of the gynecologic condition adenomyosis.MethodsA PubMed, Web of Science, and CINAHL search was undertaken. Citations were limited to the past 30 years.ResultsThere were 223 articles identified, with 31 articles being the basis of this review. Adenomyosis is a relatively common gynecologic condition that was previously thought to predominantly occur in older women, as it was diagnosed most commonly after a hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(181 reference statements)
1
9
0
Order By: Relevance
“…For this reason, some researchers tried to summarize the current evidence on the risks associated with adenomyosis during pregnancy in several literature reviews, such as the ones carried out by Harada et al [ 27 ], Buggio et al [ 28 ], and Wendel et al [ 29 ]. However, these papers just reviewed the literature and speculated about the potential mechanisms that explain why adenomyosis can produce poorer obstetrical outcomes [ 27 ] and highlighted several methodological drawbacks of the studies reported, such as poor design, small sample size, high qualitative heterogeneity, potential misclassification bias, and co-morbid conditions; this prevents drawing definitive conclusions on the strength of the observed associations and on the magnitude of the treatment effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, some researchers tried to summarize the current evidence on the risks associated with adenomyosis during pregnancy in several literature reviews, such as the ones carried out by Harada et al [ 27 ], Buggio et al [ 28 ], and Wendel et al [ 29 ]. However, these papers just reviewed the literature and speculated about the potential mechanisms that explain why adenomyosis can produce poorer obstetrical outcomes [ 27 ] and highlighted several methodological drawbacks of the studies reported, such as poor design, small sample size, high qualitative heterogeneity, potential misclassification bias, and co-morbid conditions; this prevents drawing definitive conclusions on the strength of the observed associations and on the magnitude of the treatment effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They observed an increased risk for spontaneous abortion (OR: 3.49, 95% CI: 1.41–8.65), pre-eclampsia (OR: 7.87, 95% CI: 1.26–49.20), small for gestational age (OR: 3.90, 95% CI: 2.10–7.25), preterm delivery (OR: 2.74, 95% CI: 1.89–3.97), and cesarean section (OR: 2.62, 95% CI: 1.00–6.89). Nirgianakis et al reported more recently another meta-analysis on seventeen studies comprising 1115 women diagnosed as having adenomyosis and 96,225 controls [ 29 ]. These authors observed an increased risk for spontaneous abortion (OR: 2.50, 95% CI: 1.26–4.95), pre-eclampsia (OR: 4.32, 95% CI: 1.68–11.09), small for gestational age (OR: 2.10, 95% CI: 1.17–3.77), preterm delivery (OR: 2.63, 95% CI: 1.96–3.54), and cesarean section (OR: 4.44, 95% CI: 2.64–7.46).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy patients with adenomyosis have a high rate of miscarriage. [ 13 ] Therefore, pregnancy related to adenomyosis is a very difficult problem.…”
Section: Discussionmentioning
confidence: 99%
“…Adenomyosis is also known to be associated with unfavorable pregnancy outcomes, such as an increased incidence of second-trimester miscarriages, preterm prelabor rupture of membrane (pPROM), preterm delivery, preeclampsia, and small for gestational age infants (SGA). 3 , 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 10 , It is unknown how the removal of the adenomyotic lesion affects pregnancy outcomes, and the only 2 studies that followed pregnancies after an adenomyomectomy and other case reports and case series suggested that these women are at risk for uterine rupture and early miscarriage. 7 , 11 , 12 However, the actual risk for uterine rupture has not been elucidated because of the lack of previous reports and nor has the effects of adenomyomectomy on pregnancy outcomes, such as pPROM, preeclampsia, and SGA, in comparison with women with adenomyosis. To evaluate the effects of an adenomyomectomy on pregnancy outcomes, we retrospectively compared the pregnancy outcomes of women who underwent adenomyomectomy before conception with those of women with adenomyosis.…”
Section: Introductionmentioning
confidence: 99%